(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article talks about the function of logical emphasis in the process of speech communication. In particular, emphasis serves to distinguish the dictum and modus parts of the sentence and to express the speaker’s purpose and attitude. Joy, displeasure, anger, hatred, sadness are among them.